Clinical and immunological findings in 104 cases of paraneoplastic pemphigus. (1st December 2015) - Ohzono, A.; Sogame, R.; Li, X.; Teye, K.; Tsuchisaka, A.; Numata, S.; Koga, H.; Kawakami, T.; Tsuruta, D.; Ishii, N.; Hashimoto, T.
Summary: Background: Although there are many reports of sporadic patients with paraneoplastic pemphigus (PNP), only a few systematic studies on large cohorts of patients with PNP have been reported. Objectives: To analyse the clinical and immunological findings in a large cohort of patients with PNP. Methods: This retrospective study consisted of 104 patients with PNP. Clinical and histopathological manifestations, associated neoplasms, complicating diseases, prognosis and results of immunofluorescence, immunoblotting and enzyme‐linked immunosorbent assays (ELISAs) were analysed. Results: The clinical and histopathological findings in this study were generally similar to those in previous reports. The most common associated neoplasms included malignant lymphomas, malignant solid tumours and Castleman disease, in that order, while 12 patients had no detectable tumours. Novel ELISAs for desmocollins (Dscs) showed that 19 (18·6%), 42 (41·2%) and 62 (60·8%) of 102 patients with PNP showed antibodies to Dsc1, Dsc2 and Dsc3, respectively. Thirty‐two (60%) of 53 patients had antibodies to alpha‐2‐macroglobulin‐like protein 1 (A2ML1). We found statistically significant correlations between positive desmoglein 3 reactivity and genital lesions, and between positive desmoglein 3 reactivity and bronchiolitis obliterans. Conclusions: We consider that antibodies to Dscs and A2ML1 are useful for the diagnosis of PNP.